Analysis of the effective leadership style of madrasa heads in the 21st century - Muh Syauqi Malik; Tutut Hilda Rahma; Vifta Agnia Utami (Prodi PGMI IAIN Salatiga, 2021)
One of the government's policies in education in the 21st century is the enactment of educational autonomy. This policy needs to be accompanied by a change of leadership in the education unit. The leadership qualities of the head of the madrasah will determine whether the madrasah achieves its expected goals or not. The purpose of this research is to analyze outstanding leadership in the 21st century, which includes the characteristics, style, nature, requirements, quality, and competence that a madrasah head must possess. This research was conducted at SDN 5 Cileungsir, Ranch Subdistrict, Ciamis Regency, in March 2020. This research used a library study approach. The data used in this research is secondary data, as the techniques carried out are collecting various credible sources from books, written documents, and articles taken from quality national and international online journals and have been accredited. All references that the author provides in this article aim to inform the reader of the tips and requirements to be an ideal and competent leader in the 21st century, especially leaders in schools. All descriptions are equipped with explanations and examples of events that are often encountered in the field to be understood easily. Based on the research results, it can be concluded that a leader must display exemplary behavior in the madrasah he leads. The behavior of the head of the madrasah must reflect the high spirit of work and should be an example or role model for all people in madrasahs. The ideal educational leader of the 21st century is an innovative leader, a leader who can innovate, has managerial skills and technical skills, and is highly dedicated to what he leads. Managerial expertise is needed for leaders to handle the complexities of educational institutions, and educational leadership skills are needed to obtain innovative leaders in leading educational institutions to conform to a 21st-century education. He must have the vision, mission, willingness, and commitment to make changes, progress, understand processes, and create innovations and solutions. Besides, a leader must also have expertise and quality. Thus, if a leader can realize all these components, then the madrasah under its management can innovate better under the demands of education in the 21st century and per the objectives to be achieved.